Effect of Workload and Leadership on Turnover Intention with Job Satisfaction as A Mediation Variable on Employees of PT. World Innovative Telecommunications - Karunia Abdi Islamy; Elok Damayanti; Hermien Tridayanti; Bayu Airlangga Putra (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2021)
This study discusses how the influence of workload and leadership on turnover intention with job satisfaction as a mediating variable on employees of PT. World Innovative Telecommunications (Oppo Street East Surabaya). This study aims to determine the effect of workload and leadership on turnover intention with job satisfaction as a mediating variable on employees of PT. World Innovative Telecommunications (Oppo Street East Surabaya). This type of research uses a quantitative approach. Collecting data using observations and distributing questionnaires. The sampling technique in this study was using the census method or saturated sample. The population in this study were employees of PT. World Innovative Telecommunications (Oppo Street Surabaya Timur) as many as 81 respondents. The analytical method used is PLS (Partial Least Square). Based on the results of this study, Workload and Leadership on Turnover Intention through the Job Satisfaction variable did not have a significant effect or the Job Satisfaction variable did not mediate the effect of Workload and Leadership on the Turnover Intention of employees in this company.